The Effects of Environmental Sustainability Labels on Selection, Purchase, and Consumption of Food and Drink Products: A Systematic Review. Issue 8 (October 2021) - Potter, Christina; Bastounis, Anastasios; Hartmann-Boyce, Jamie; Stewart, Cristina; Frie, Kerstin; Tudor, Kate; Bianchi, Filippo; Cartwright, Emma; Cook, Brian; Rayner, Mike; Jebb, Susan A.
This review assessed the effects of environmental labels on consumers' demand for more sustainable food products. Six electronic databases were searched for experimental studies of ecolabels and food choices. We followed standard Cochrane methods and results were synthesized using vote counting. Fifty-six studies ( N = 42, 768 participants, 76 interventions) were included. Outcomes comprised selection ( n = 14), purchase ( n = 40) and consumption ( n = 2). The ecolabel was presented as text ( n = 36), logo ( n = 13) or combination ( n = 27). Message types included: organic ( n = 25), environmentally sustainable ( n = 27), greenhouse gas emissions ( n = 17), and assorted "other" message types ( n = 7). Ecolabels were tested in actual ( n = 15) and hypothetical ( n = 41) environments. Thirty-nine studies received an unclear or high RoB rating. Sixty comparisons favored the intervention and 16 favored control. Ecolabeling with a variety of messages and formats was associated with the selection and purchase of more sustainable food products.